PERBANDINGAN RESPON FISIOLOGIS KAMBING DAN DOMBA BETINA MENYUSUI YANG DIPELIHARA PADA SISTEM PEMELIHARAAN INTENSIF - Zahra, Nadia Aulia; Hasanah, Himmatul (Jurnal Peternakan Nusantara, 2024)
The system for rearing goats (Capra aegagrus) and sheep (Ovis aries) which is widely applied by Indonesian people is generally still intensive. This intensive rearing system is the physiological adaptability of livestock, especially female livestock that are currently breastfeeding. This research aimed to determine the comparison of the physiological responses of lactating goats and ewes in an intensive rearing system. This study used a quantitative research design with the T-test to compare the physiological responses of lactating ewes and goats. There were six lactating female goats and four ewes used in this study. The results showed that the THI value of the goat and sheep pens was in the severe heat stress category, but there was no significant comparison between the THI values of the two pens (P>0.05). The ocular temperature parameters of goats and sheep do not have a significant comparison (P>0.05), the surface temperature parameters of goats and sheep also do not have a significant comparison (0>0.05), while the respiration rate parameters of goats and sheep have a significant comparison (0<0,05). The correlation coefficient value between the sheep's ocular temperature and the back temperature, namely 0.96 and the rump, namely 0.68, has a positive correlation value, so that the higher the sheep's ocular temperature, the higher the temperature of the back and rump. In conclusion, lactating ewes and goats experience stress due to severe heat stress from the environment. In addition, there was no significant physiological comparison between goats and lactating ewes that were reared intensively on the physiological response parameters of ocular temperature and surface temperature. However, there is a comparison of physiological responses to respiratory rate parameters.